SELEKSI POHON PLUS TENGKAWANG TUNGKUL (Shorea stenoptera Burck.) DI DESA SUNGAI LAWAK KECAMATAN NANGA TAMAN KABUPATEN SEKADAU - Ningrum, Intan Utami; Muin, Abdurrani; Wulandari, Reine Suci (Universitas Tanjungpura, 2018)
Tengkawang tungkul (Shorea stenoptera Burck.) in Sungai Lawak Village, Nanga Taman Sub-District of Sekadau regency has high potency and economic values. Selection of tengkawang tungkul plus tree is the first step towards obtaining stock for developing clonal and seedling orchards of superior phenotypes. The purpose of this research was to obtain plus tree of tengkawang tungkul. The research was done with survey method with exploration technique. Exploration done randomly of tengkawang tungkul and compared with comparison trees as the basis for determining the prospective plus tree. The results showed 16 individuals was identified as plus tree with 96 trees as a comparison. There were 9 trees which have the highest score of 75. The average tengkawang tungkul has a good phenotype, such as the total height of trees with a score of 20, height free branches with a score of 15, diameter with a score of 30, canopy area with a score of 10.Keywords: plus tree, selection, tengkawang tungkul